Factors Contributing to the Adoption of Quality Management Systems in the Hotel Industry in Zimbabwe - Basera, V (BUSE, 2021)
This study sought to explore factors contributing to the adoption of quality management systems (QMSs) in the hotel industry in Zimbabwe. The hotel industry lags behind regarding the adoption of QMSs. Consolidative analyses of literature was performed so as to identify the factors affecting the adoption of QMSs in the hotel industry, explore the benefits of adopting business excellence (BE) as a tool for improving quality and to identify external stakeholders influencing the adoption of QMSs. To realise the objectives of this research, the study proposed a conceptual framework as per key concepts observed as recurring during the study’s literature review analysis. The conceptual framework was used to guide the research’s investigation throughout from objectives formulation, the data collection and analysis stages. The study adopted the interpretivism paradigm and used a combination of qualitative approaches in data collection and analysis with a multiple case-study design. The study’s sample comprised of nine hotel managers, four mangers from key stakeholders [Zimbabwe Tourism Authority (ZTA), Hospitality Association of Zimbabwe (HAZ), Tourism Business Council of Zimbabwe (TBCZ) and Standards Association of Zimbabwe (SAZ)] and forty-eight staff members purposively selected from hotels in Harare. In-depth interviews and focus group discussions were used to generate data. The data were analysed using directed content analysis approach and NVivo 12 software. NVivo 12 was used in the context of setting a solid data analysis for easy comparison of themes and cross cases data. Questions of data trustworthiness were addressed. Credibility was attained by implementing suitable and recognised research methods while transferability was attained by means of the provision of contextual data to establish the background of the research. Confirmability was attained through triangulation and the provision of in-depth methodological explanation. The study revealed that the adoption of QMS in the hotel industry is affected by seven internal factors - high management turnover, high staff turnover, absence of a specialised quality function within the hotels, poor remuneration of hotel employee, shortage of financial resources, lack of product development, hotel size and seven external factors - high taxes and licensing fees, industry over-regulation, high levels of competition and low levels of coopetition, economic challenges, poor industry supporting infrastructure, corruption by authorities and lack of hotel customers’ representation. The investigation further revealed a positive relationship between business excellence and QMSs adoption with some of the hotels participating in local business excellence awards like the Zimbabwe National Chamber of Commerce (ZNCC) and others. The study further exposed that there were relatively a number of external stakeholders influencing the adoption of QMSs within the hotel industry which include local authorities, banks and industry associations and councils. The findings reflected that adoption of QMS in the hotel industry bring a number of benefits that enable the hotels to be competitive internationally and locally. The study recommends that hotels must strategically plan for the adoption of QMSs using a multi-stakeholder approach. The study also recommends that hotels need to come up with standard operating procedures and quality policy documents which can be used for reference by their employees and also need to comprehend physical aspects of service quality. A model for adopting QMSs in the hotel industry was developed to assist policy makers address the adoption of QMSs in the hotel industry and in other industries. While this study adopted a qualitative methodology, for further research, the study recommends the adoption of a quantitative method in data collection and analysis of the results.
Keywords: hotel; hotel industry; quality management; quality management systems; adoption; factors